The Potential of Solar Energy as a Driver of Regional Development - Challenges and Opportunities - Marolin, Mario; Drvenkar, NataÅ¡a; UnukiÄ‡, Ivana (International Journal of Energy Economics and Policy, 2020)
Dependence on energy products, especially on fossil fuels, greatly affects the long-term development and diplomatic capabilities of any country. The EU has been allocating considerable funds to strengthen its cohesion, promote balanced development in the different regions, support investments in renewable energy sources, and gain energy independence. The funds earmarked by the EU for these types of investments have the potential to be the main drivers of long-term sustainable economic growth and development, thus enhancing cohesion. Investing in renewable energy sources, in particular in the solar energy, can spur the growth and development of other sectors, attract new investments and thus strengthen the capacity for providing social support to the most vulnerable population. For underdeveloped regions, this would mean new opportunities and investments while preserving the environment for future generations. Implementing sustainable solutions might be relatively simple, given that regulatory, economic, as well as natural and infrastructure components exist. This is evidenced by a significant body of research, which provides a robust basis for a development model based on the investment potential of solar energy to address the issue of regional disparities in the EU and its energy dependence. Keywords: renewable energy sources, energy efficiency, solar energy, regional development JEL Classifications: O21, O380, R280 DOI: https://doi.org/10.32479/ijeep.10068